2006
DOI: 10.7861/clinmedicine.6-1-61
|View full text |Cite
|
Sign up to set email alerts
|

Working the night shift: preparation, survival and recovery - a guide for junior doctors

Abstract: -Following the implementation of the European Working Time Directive Regulations, almost all junior doctors in the UK now work full night-shifts. An RCP 50-member working group was established to develop a practical guide to help junior doctors prepare, survive and recover from working night shifts. The guide, set out in this paper, examines the evidence concerning the hazards of shiftwork, and techniques that can be used to reduce risk. The main advice is to minimise sleep debt by taking additional two-hour s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 26 publications
0
49
0
1
Order By: Relevance
“…Guidelines issued by the UK's Royal College of Physicians suggest that for every 2 nights on duty, ≥1 whole day off should be scheduled (20). The current analysis indicated that 1 day of rest following a block of 3 or 4 nights resulted in the spillover of fatigue effects into the first subsequent day shift.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Guidelines issued by the UK's Royal College of Physicians suggest that for every 2 nights on duty, ≥1 whole day off should be scheduled (20). The current analysis indicated that 1 day of rest following a block of 3 or 4 nights resulted in the spillover of fatigue effects into the first subsequent day shift.…”
Section: Discussionmentioning
confidence: 87%
“…Although the new work schedules conformed to the Directive's stipulations (eg, a minimum daily rest period of 11 hours), they failed to take into account other parameters that, although not covered by the EWTD, are nevertheless vital considerations in the management of fatigue. The current findings highlight some of these additional parameters, building upon previously published recommendations regarding the design of doctors' working hours and provision of services (20,33,34). One of the unique and crucial contributions of this study is its provision of evidence to support such recommendations, based on junior doctors own experiences of working on EWTD-compliant shift rotas.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 General practitioners refer patients directly to the acute medical unit (AMU) and heart emergency centre (HEC) for assessment. 15 The accident and emergency department (A&E) refers medical admissions to HEC, AMU, medical wards and the intensive care unit (ITU) via the on-call medical specialist registrar (Spr).…”
Section: Methodsmentioning
confidence: 99%
“…In the UK, the Royal College of Physicians (Horrocks and Pounder, 2006) have recently produced guidelines for junior doctors that reinforce what many nurses have discovered for themselves, but are still very useful: associate your bedroom with sleep do not watch TV or use computers there; before your first night lie in late and take an afternoon nap (2 h); take a nap during the night (20-45 min but no more than 45); maximise your exposure to bright light during the night (desk lamp/overhead lights); eat and drink properly, do not start the shift hungry or dehydrated; small amounts of caffeine can be used to maintain alertness; when you get home go straight to bed; avoid alcohol and sleeping tablets to aid sleep.…”
mentioning
confidence: 99%